ChemInform Abstract: Polyarylene Synthesis by Cross‐Coupling with HOMSi Reagents. Issue 25 (3rd June 2013) - Shimizu, Kenta; Minami, Yasunori; Nakao, Yoshiaki; Ohya, Ken‐ichiro; Ikehira, Hideyuki; Hiyama, Tamejiro
Abstract Cross‐coupling reactions of dibromoarenes (I), (IV), and (VI) with HOMSi reagents (organo[2‐hydroxymethylphenyl]dimethylsilanes) (II) or alternatively bromoarenes (IX) and arylene‐bisHOMSi reagents, e.g. (VIII), afford ter‐ or quaterarenes (III), (V), (VII), and (X), resp., in high yields.